2013
DOI: 10.1080/09297049.2012.753998
|View full text |Cite
|
Sign up to set email alerts
|

Few differences in hot and cold executive functions in children and adolescents with combined and inattentive subtypes of ADHD

Abstract: The aim of the study was to compare executive processes with pronounced (hot) and less pronounced (cold) emotional salience in medication naïve children and adolescents with ADHD-combined (ADHD-C) and ADHD-inattentive (ADHD-I) subtypes. Thirty-six subjects with ADHD-C, 44 with ADHD-I, and 50 healthy controls between 8 and 17 years were assessed with laboratory tests and inventory-based scales assessing hot and cold executive functions (EF) (controlled attention, working memory, planning, cognitive flexibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 130 publications
(212 reference statements)
9
49
0
13
Order By: Relevance
“…Contrary to our expectations, there were no between-group differences on the hot decision-making task across time. No between-group differences on hot decision-making performance have previously been reported in TD children and children with ADHD (10-12 years) (Geurts et al, 2006;Lambek et al, 2010;Masunami, Okazaki, & Maekawa, 2009;Skogli, Egeland, et al, 2013). Toplak et al (2005) found impaired decision-making in adolescents (15 years) with ADHD relative to TD adolescents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Contrary to our expectations, there were no between-group differences on the hot decision-making task across time. No between-group differences on hot decision-making performance have previously been reported in TD children and children with ADHD (10-12 years) (Geurts et al, 2006;Lambek et al, 2010;Masunami, Okazaki, & Maekawa, 2009;Skogli, Egeland, et al, 2013). Toplak et al (2005) found impaired decision-making in adolescents (15 years) with ADHD relative to TD adolescents.…”
Section: Discussionmentioning
confidence: 96%
“…Detailed recruitment strategy and diagnostic assessment are described in detail in separate publications (Hovik, Plessen, Skogli, Andersen, & Oie, 2013;Skogli, Egeland, et al, 2013) and only a short presentation will be given here. Demographic characteristics are presented in Table 1.…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…Los resultados mostraron que hubo signifi cativamente menos patrones de tiempo, incluidas las sanciones, en los niños con TDAH en comparación con los controles, lo que indicaría que los niños con TDAH son menos sensibles a las sanciones, prestando menos atención a las mismas que los del grupo control. Skogli et al (2013) realizaron el estudio en niños y adolescentes con TDAH de subtipo combinado (TDAH-C), subtipo inatento (TDAH-I), y un grupo control, y si bien no encontraron diferencias signifi cativas, observaron elecciones más desventajosas en los niños menores de 12 años y un mejor rendimiento de TD a medida que aumentaba la edad, lo que podría explicarse como un efecto del desarrollo.…”
Section: Resultsunclassified
“…En sentido contrario, el 75% (6 de 8) de los estudios que trabajaron con muestras mixtas de niños y de adolescentes no encontraron diferencias en las medias de los desempeños de ambos grupos (Hovik et al, 2015;Lambek et al, 2011;Masunami et al, 2009;Scheres et al, 2006;Skogli et al, 2014;Skogli et al, 2013). Y la totalidad de los estudios (3) que analizaron sólo el desempeño en adolescentes (Kroyzer et al, 2014;Pollak y Shoham, 2015;Toplak et al, 2005), encontraron evidencias de un desempeño inferior de los jóvenes con TDAH.…”
Section: Discussionunclassified
See 1 more Smart Citation